Just enough AutoCAD 2006 - Omura, George (SYBEX, 2005)
Your Guide to Essential AutoCAD Techniques Award-winning and best-selling AutoCAD author George Omura has developed this practical reference to help you learn AutoCAD basics easily and efficiently. His straightforward explanations and realistic exercises focus squarely on accomplishing vital tasks. Whether you're completely new to AutoCAD or you're looking for a quick refresher to perform a particular task, Just Enough AutoCAD 2006 provides the authoritative instruction you need. You'll become familiar with the drafting tools of AutoCAD and AutoCAD LT and learn how to: Draw accurately and quickly Effectively edit AutoCAD drawings Create 3D models Get organized with layers, blocks, groups, and external references Efficiently add and edit notes and dimensions Find areas and distances quickly Extract hidden data